Modeling Gum Metal and other newly developed titanium alloys within a new class of constitutive relations for elastic bodies - Kulvait, V.; Málek, J.; Rajagopal, K.R. (Archives of Mechanics, 2017)
Many titanium alloys and even materials such as concrete exhibit a nonlinear relationship between strain and stress, when the strain is small enough that the square of the norm of the displacement gradient can be ignored in comparison to the norm of the displacement gradient. Such response cannot be described within the classical theory of Cauchy elasticity wherein a linearization of the nonlinear strain leads to the classical linearized elastic response. A new framework for elasticity has been put into place in which one can justify rigorously a nonlinear relationship between the linearized strain and stress. Here, we consider one such model based on a power-law relationship. Previous attempts at describing such response have been either limited to the response of one particular material, e.g. Gum Metal, or involved a model with more material moduli, than the model considered in this work. For the uniaxial response of several metallic alloys, the model that is being considered fits experimental data exceedingly well.